THE PLACE AND ROLE OF UNMANNED FLIGHT VEHICLES IN MODERN ARMED CONFLICT. (Multidisciplinary Journal of Science and Technology, 2025)
This article discusses group intelligence behavior, the use of unmanned systems called "drones", swarm intelligence and military intelligence observed in nature, ways to use the military drone "Swarm" in combat, the importance of human-AI cooperation, human control for AI necessity, improvement of command and control structures was discussed.